Synthesis and thermal characterization of novel phase change materials (PCMs) of the Se–Te–Sn–Ge (STSG) multi-component system: calorimetric studies of the glass/crystal phase transition. Issue 14 (22nd March 2019) - Pal, Shiv Kumar; Chandel, N.; Mehta, N.
Abstract : According to recent literature, germanium-containing chalcogenide glasses (ChGs) show improvement in thermal stability and glass-forming ability because of the self-organization of the glass network towards a more rigid structure. Abstract : According to recent literature, germanium-containing chalcogenide glasses (ChGs) show improvement in thermal stability and glass-forming ability because of the self-organization of the glass network towards a more rigid structure. The Ge-containing ChGs play a potential role as PCMs in phase-change optical memory (PCOM) applications. This endeavor reports the synthesis of some novel PCMs with Ge as the chemical modifier to improve the kinetic parameters of glass/crystal phase transition. The compositional variation of the various kinetic parameters in the present STSG chalcogen-rich non-oxide glasses Se78− y Ge y Te20 Sn2 (0 ≤ y ≤ 6) has been studied by means of the state-of-the-art differential scanning calorimetric (DSC) technique in the non-isothermal mode. The thermally assisted glass transition and crystallization phenomena have been investigated by examining the variation in various kinetic parameters like the characteristic kinetic temperatures (glass transition temperature T g, on-set crystallization temperature T o and peak crystallization temperature T c ), the activation energies involved in both phenomena, the thermal stability factor S and the glass-forming ability (GFA). The thermal stability factor S and GFA increase appreciably at higher concentrations of Ge as a signature of stiffness transition followed by the self-organization of the corner-sharing and the edge-sharing arrangements of the GeSe4 phase.